2019
DOI: 10.1016/j.cmi.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory virus infection among hospitalized adult patients with or without clinically apparent respiratory infection: a prospective cohort study

Abstract: a b s t r a c tObjectives: To determine the viral epidemiology and clinical characteristics of patients with and without clinically apparent respiratory tract infection. Methods: This prospective cohort study was conducted during the 2018 winter influenza season. Adult patients with fever/respiratory symptoms (fever/RS group) were age-and sex-matched with patients without fever/RS (non-fever/RS group) in a 1:1 ratio. Respiratory viruses were tested using NxTAG™ Respiratory Pathogen Panel IVD, a commercially-av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
1
24
1
Order By: Relevance
“…Our network pathway enrichment analysis showed that steroid-related pathways are enriched. RV is more likely to be associated with acute exacerbation of asthma than influenza virus infection (To et al, 2019). A previous study has shown that RV infection leads to steroid-resistance in airway epithelium (Papi et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Our network pathway enrichment analysis showed that steroid-related pathways are enriched. RV is more likely to be associated with acute exacerbation of asthma than influenza virus infection (To et al, 2019). A previous study has shown that RV infection leads to steroid-resistance in airway epithelium (Papi et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…This baseline is important as reliance on case counts alone can overlook subclinical infections, which are common for SARS-CoV-2 and other respiratory viruses. 30 In addition to monitoring the prevalence of subclinical infections, continuous monitoring of seroprevalence will help to establish the level of herd immunity in the population.…”
Section: Discussionmentioning
confidence: 99%
“…If patients were intubated, we obtained endotracheal aspirate instead of posterior oropharynx saliva. 6,[9][10][11] Our initial experience showed that such saliva samples are promising in viral load monitoring in patients with COVID-19. 6 We also retrieved serum remnant from blood samples taken for routine bio chemical testing, and refrigerated these samples at -20°C until antibody testing could be done.…”
Section: Methodsmentioning
confidence: 99%